THE USE OF GUESSING GAME IN TEACHING SPEAKING : AN EXPERIMENTAL STUDY OF SECOND GRADE STUDENTS AN SMKN 2 BANDUNG - Mega Dwi Martiani, - (2009)
ABSTRACT There were two burning issues in this study, namely Guessing Game and students' speaking ability. Based on those issues, to improve students' speaking ability, speaking should be learned through meaningful technique. Meanwhile, most students even in Senior High School level were still facing many obstacles to speak English fluently. To overcome that problem, one of alternative technique applied was by having a game. Guessing Game was considered to apply because in this game, students were expected to be involved actively in speaking class activity. This study was aimed to investigate the use of Guessing Game in improving students' speaking ability, and to find out the advantages, disadvantages of the technique, and strategies used to overcome the obstacles in learning speaking by using the technique. Quasi experimental design was used in this study with pre-test and post-test non equivalent groups design. Two classes of the second grade students in SMKN 2 Bandung were chosen as the samples in this study. In addition, interview was given to obtain further information about the technique. The findings of this study suggested that Guessing Game was effective in improving students' speaking ability. As indicated by a statistically higher speaking test scores of experimental (M = 7.251, SE = 1.252) than those of the control group (M = 5.714, SE = 12.47). This difference was highly significant with t(33) = 14.347, p<.05 and effect size value of r = 0.94. In addition, the results of interview showed that joyful learning became the advantage of the technique. Inappropriate clues arrangement was revealed to be the disadvantage, and vocabulary memorizing was stated as the strategies used to overcome the obstacles in learning speaking by using Guessing Game. In reference to the result of this study, the conclusion was drawn that Guessing Game technique is appropriate to apply in classes which have many varieties of students' characteristics. In addition, English teachers are recommended to apply Guessing Game technique in teaching speaking. Further researchers in the same field of study are suggested to find another technique in improving students' speaking ability.